2023
DOI: 10.1111/dar.13617
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parental alcohol problems and later dropout and grade point average in high school: A register‐based follow‐up study

Abstract: Introduction:The aim of the study was to test the hypothesis that young people with perceived parental alcohol problems have higher dropout rates in high school and lower grade point average (GPA) at graduation compared to young people without perceived parental alcohol problems. Methods: Data come from Danish National Youth Study 2014 (n = 62,171), merged with register-data on later dropout of high school and GPA. Multilevel Poisson regression models of incidence rates of dropout and multilevel linear models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Second, with regards to the students in grade 11 in our sample, there may be an additional bias as upper secondary school is not mandatory in Sweden. Although the majority of adolescents enrol in upper secondary school, it is likely that students with problematic familial alcohol use are more inclined to not continue to or to drop out from upper secondary school ( Pisinger et al, 2023 ). Relatedly, this group of adolescents probably also have more psychosomatic complaints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, with regards to the students in grade 11 in our sample, there may be an additional bias as upper secondary school is not mandatory in Sweden. Although the majority of adolescents enrol in upper secondary school, it is likely that students with problematic familial alcohol use are more inclined to not continue to or to drop out from upper secondary school ( Pisinger et al, 2023 ). Relatedly, this group of adolescents probably also have more psychosomatic complaints.…”
Section: Discussionmentioning
confidence: 99%
“…One particular type of adversity relates to alcohol problems in the family of origin ( Felitti et al, 1998 ). Children of problem-drinking parents have increased risks of short- and long-term adverse outcomes in terms of, e.g., higher levels of drinking and more problematic drinking themselves ( Haugland et al, 2013 , Karlsson et al, 2016 , Olssonet al, 2019 , Olsson et al, 2021 , Pisinger et al, 2017 , Thor et al, 2022 ), higher levels of self-reported health problems ( Pisinger et al, 2016 , Wahlström et al, 2023a ), increased risks of mental and behavioural disorders ( Johnson and Leff, 1999 , Landberg et al, 2019 , Raitasalo et al, 2019 ), as well as poorer educational outcomes ( Berg et al, 2016 , Pisinger et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…These investigations emphasize the risk that inequalities in access to education that already existed prior to the pandemic have increased (Bayley et al, 2023). On the other hand, there remains a high interest in continuing to delve into the causes that cause it, either in a general way (Kumar et al, 2023) or by analyzing specific factors such as parental alcohol consumption (Pisinger et al, 2023). Some studies analyze this topic using more sophisticated techniques, such as machine learning (Colak Oz et al, 2023;Selim & Rezk, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These children face an elevated risk of experiencing adverse social and physical consequences such as neglect, abuse, and dysfunctional family environments ( Dube et al, 2001 , Haugland et al, 2021 , Jose and Cherayi, 2020 ). They also tend to exhibit higher rates of self-reported health problems ( Pisinger et al, 2017 , Wahlström et al, 2023 , Syed Raza et al, 2023 ), increased risks of mental and behavioural problems ( Johnson and Leff, 1999 , Landberg et al, 2019 , Raitasalo et al, 2019 ), and lower educational attainment ( Berg et al, 2016 , Pisinger et al, 2023 ). Moreover, children with parents who have alcohol problems are more likely to develop alcohol dependency themselves compared to other children in the same society ( Johnson & Leff, 1999 ).…”
Section: Introductionmentioning
confidence: 99%